Aging voice and the laryngeal muscle atrophy - Martins, Regina Helena Garcia [UNESP]; Pessin, Adriana Bueno Benito [UNESP]; Nassib, Douglas Jorge [UNESP]; Branco, Anete [UNESP]; Rodrigues, Sergio Augusto; Matheus, Selma Maria Michelim [UNESP] (Wiley, 2015)
To study by means of morphometric measurements the severity of vocal muscle atrophy in the elderly. Cadaver study. Universidade Estadual Paulista (UNESP), Botucatu Medical School, Brazil. Thirty vocal folds were collected from necropsies distributed into three groups: aged 60 to 75 years (n = 10); aged 76 to 90 years (n = 10); and a control group aged 30 to 50 years (n = 10). Specimens for histology were obtained from the middle portion of the vocal folds. The stained specimens were analyzed using Axion Vision software (coupled to a Zeiss [Oberkochen, Germany] microscope) and used in the morphometric analyses conducted with the ImageJ software. The diameters of 200 muscle fibers from each slide were measured, and the mean values were statistically analyzed. The mean values of the diameters of the vocal muscle fibers of the elderly age groups were smaller than in the control: control (30-50 years: 16.389 μm); elderly (60-75 years: 14.412 μm; 76-90 years: 14.162 μm) (P < 0.01). No statistical differences were observed between genders. The morphometric analysis showed smaller diameters of vocal muscle fibers in the elderly when compared to controls, demonstrating the atrophy of the muscle. No statistical differences were observed between genders. N/A. Laryngoscope, 125:2518-2521, 2015.
Keywords: Larynx; Morphometry; Presbyphonia; Vocal muscle; Voice